The Influence of Green Corporate Social Responsibility and Green Innovation on Company Value - Nirwansyah, Moch; Susandra, Farizka; Anwar, Saepul (Institut Bisnis dan Informatika Kesatuan, 2025)
This study aims to analyze the effect of Green Corporate Social Responsibility (GCSR) and Green Innovation on company value in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2022 period. GCSR is a form of corporate social responsibility towards the environment, while Green Innovation includes innovation in environmentally friendly products and processes. The research data were obtained from annual reports and corporate sustainability reports, then analyzed using multiple linear regression methods with the help of SPSS 25 software. The results of the study show that GCSR has a negative and insignificant effect on company value, indicating that spending on social responsibility has not significantly increased company value. Conversely, Green Innovation has a positive and significant effect on company value, indicating that environmentally friendly innovation can increase the company's competitiveness and financial performance. Simultaneously, GCSR and Green Innovation have a positive and significant effect on company value, although the contribution of GCSR is relatively small compared to Green Innovation. This study highlights emphasize the importance of companies to focus more on green innovation in increasing company value, as well as the need for a more effective GCSR implementation strategy in order to have a tangible impact on business sustainability.